Aplicación móvil de apoyo en la calibración de equipos biomédicos de masa y presión según la norma ISO/IEC 17025:2017 (2025)
This degree work addresses the development of a mobile application intended to support the calibration processes of mass and pressure measurement equipment, in accordance with the ISO/IEC 17025:2017 standard. This project is justified by the various accessibility and customization deficiencies observed in the applications available on the market, as well as the time and resource-consuming manual practices for generating certificates. To achieve this, multiple calibrations were carried out in collaboration with the Novamedical S.A.S. laboratory, where several deficiencies in the processes and certificates were identified. The application, named Solva Metrics, was developed using Android Studio with the Java programming language, implementing 21 classes that defined the software's behavior. Online and offline databases were implemented for login and storage of equipment due for calibration, respectively. The application allows for the customization of calibration certificates to be used by any laboratory and stores important information to streamline the certificate generation process. During its development, various requests and changes proposed by the laboratory were properly received and addressed. Finally, field tests demonstrated that the application significantly reduces the time required to generate certificates compared to the commonly used manual method.